Temperature control using a microcontroller - Yang, Yikuan (2012)
For over 40 years, oven industries have specialized in the design and manufacture of custom temperature controllers, electronic control systems and temperature sensors. Temperature control has become a relatively mature technology. This project aimed to develop a temperature control system which will be used to control the temperature inside a small oven case for some special applications based on microchip PIC microcontroller. Through reviewing past and current temperature control studies, the author finally established a control system with heating and cooling functions according to the ambient temperature it sensed. In this report, the design process of the temperature control system and how it works to achieve the goal of temperature controlling are elaborated.